Traducción Y Subversión: Traduciendo La Voz Femenina. Una Nueva Interpretación De La Poesía Traducida De Adrienne Rich - (:unkn) unknown (My University, 2014)
This thesis intends to prove how close politics and poetics are in Adrienne Rich's works, to the point that they often become indistinguishable. When this overlap occurs, while the author makes the intentions of her work and her language explicit within her works, essays or public speeches/declarations in English (as she defends her creation of a language for women), some of the translations of her work into Spanish find problematic to follow the intentions present in the English. This thesis explores the reasons for that and concludes that, due to some characteristics of Spanish morphology, such as genderization, the translation of some of Adrienne Rich's poems to Spanish ends up conveying a message that appears inconsistent with Rich's own words about the message of her texts. This will lead to offer a an analysis of the ideological implications that the different messages conveyed have in the target language, and how can the translator solve these inconsistencies.
Keywords: Adrienne Rich; Estudios Femeninos; Literatura Estadounidense; Subversión; Traducción; Translation